Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia - Donascimiento, Carlos; Cárdenas-Bautista, Johann-Stephens; Acosta, Kevin Giancarlo Borja; González-Alvarado, Arturo; Medina, Claudia A. (Zootaxa, 2016)
The catalog of type specimens of freshwater fishes deposited in the Colección de Peces Dulceacuícolas del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P) is presented. This list includes 483 specimens in 65 lots representing 11 holotypes and 472 paratypes of 48 nominal species. Corrections, additions, and updating of information in the original descriptions are included in individual remarks for each catalog number entry and a gallery of pictures of holotypes or paratypes of each nominal species is also presented, which supplements some original descriptions lacking figures of their respective types. An online version of the catalog is available at http://humboldt.org.co/en/servicios/colecciones-biologicas/catalogo-de-tipos.